A Review to AC Modeling and Transfer Function of DC-DC Converters - Rahim Ildarabadi; Azadeh Ahmadi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In this paper, AC modeling and small signal transfer function for DC-DC converters are represented. The fundamentals governing the formulas are also reviewed. In DC-DC converters, the output voltage must be kept constant, regardless of changes in the input voltage or in the effective load resistance. Transfer function is the necessary knowledge to design a proper feedback control such as PID control to regulate the output voltage as linear PID and PI controllers are usually designed for DC-DC converters using standard frequency response techniques based on the small signal model of the converter.DOI:  http://dx.doi.org/10.11591/telkomnika.v13i2.7033